SYNTHESIS OF N-[4-({4-[(5-METHYL-1, 3, 4-THIADIAZOL-2-YL)SULFAMOYL] PHENYL}SULFAMOYL)PHENYL]AMINE: AN IMPURITY IN THE ANTIBACTERIAL DRUG SULFAMETHIZOLE (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The process for the preparation of antibacterial compound 4-amino-N-(5-methyl-1, 3, 4-thiadiazol-2-yl)benzenesulfonamide (Sulfamethizole) 4 involves the reaction of 2-amino-5-methyl-1, 3, 4-thiadiazole 1 with 4-acetamidobenzenesulfonyl chloride 2 followed by alkaline hydrolysis of the intermediate N-{4-[(5-methyl-1, 3, 4-thiadiazol-2-yl)sulfamoyl]phenyl}acetamide 3. The HPLC analysis of sulfamethizole showed the formation of an impurity which was isolated and identified as N-[4-({4-[(5-methyl-1, 3, 4-thiadiazol-2-yl) sulfamoyl] phenyl} sulfamoyl) phenyl] amine 6. This impurity is the result of the reaction of unreacted sulfonyl chloride 2 with sulfamethizole to form N-[4-({4-[(5-methyl-1, 3, 4-thiadiazol-2-yl)sulfamoyl]phenyl}sulfamoyl)phenyl]acetamide 5 followed by alkaline hydrolysis of the acetamido group. The structure was further confirmed by independent synthesis.